Polyacrylamide Gels for Invadopodia and Traction Force Assays on Cancer Cells - Jerrell, Rachel J. (J Vis Exp, 2015)
Rigid tumor tissues have been strongly implicated in regulating cancer cell migration and invasion. Invasive migration through cross-linked tissues is facilitated by actin-rich protrusions called invadopodia that proteolytically degrade the extracellular matrix (ECM). Invadopodia activity has been shown to be dependent on ECM rigidity and cancer cell contractile forces suggesting that rigidity signals can regulate these subcellular structures through actomyosin contractility. Invasive and contractile properties of cancer cells can be correlated in vitro using invadopodia and traction force assays based on polyacrylamide gels (PAAs) of different rigidities. Invasive and contractile properties of cancer cells can be correlated in vitro using invadopodia and traction force assays based on polyacrylamide gels (PAAs) of different rigidities. While some variations between the two assays exist, the protocol presented here provides a method for creating PAAs that can be used in both assays and are easily adaptable to the user’s specific biological and technical needs.